Identification and Evaluation of (Non-)Intentionally Added Substances in Post-Consumer Recyclates and Their Toxicological Classification - Christian Rung; Frank Welle; Anita Gruner; Arielle Springer; Zacharias Steinmetz; Katherine Munoz (Recycling, 2023)
According to the European circular economy strategy, all plastic packaging placed on the market by 2030 has to be recyclable. However, for recycled plastics in direct contact with food, there are still major safety concerns because (non-)intentionally added substances can potentially migrate from recycled polymers into foodstuffs. Therefore, the European Food Safety Authority (EFSA) has derived very low migration limits (e.g., 0.1 µg/L for recycled polyethylene terephthalate (PET) and 0.06 µg/L for recycled high-density polyethylene (HDPE)) for recycled polymers. Thus, the use of recyclates from post-consumer waste materials in direct food contact is currently only possible for PET. A first step in assessing potential health hazards is, therefore, the identification and toxicological classification of detected substances. Within this study, samples of post-consumer recyclates from different packaging-relevant recycling materials (HDPE, LDPE, PE, PP, PET, and PS) were analyzed. The detected substances were identified and examined with a focus on their abundance, toxicity (Cramer classification), polarity (log P values), chemical diversity, and origin (post-consumer substances vs. virgin base polymer substances). It was demonstrated that polyolefins contain more substances classified as toxic than PET, potentially due to their higher diffusivity. In addition, despite its low diffusivity compared to polyolefins, a high number of substances was found in PS. Further, post-consumer substances were found to be significantly more toxicologically concerning than virgin base polymer substances. Additionally, a correlation between high log P values and a high Cramer classification was found. It was concluded that PET is currently the only polymer that complies with EFSA’s requirements for a circular economy. However, better-structured collection systems and cleaning processes, as well as more analytical methods that enable a highly sensitive detection and identification of substances, might offer the possibility of implementing other polymers into recycling processes in the future.